Machine learning for OpenCV 4 : intelligent algorithms for building image processing apps using OpenCV 4, Python, and scikit-learn /: intelligent algorithms for building image processing apps using OpenCV 4, Python, and scikit-learn. (2019) - Sharma, Aditya; Shrimali, Vishwesh Ravi; Beyeler, Michael
No abstract available